The Role of the Village Consultative Body (BPD) in Improving the Accountability in Village Governance: Case Study in Kersik Tuo Village - Ikhfal Halmaf Kholif; Ika Devi Pramudiana; Sri Kamariyah; Feri Ramadhan (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
The Village Consultative Body (BPD) plays a strategic role in overseeing the implementation of village governance to ensure transparent, participatory, and accountable governance. However, in practice, the effectiveness of the BPD's role is often influenced by various internal and external factors. This study aims to analyze the role of the BPD of Kersik Tuo Village in improving village government accountability based on the five dimensions of Servqual developed by Parasuraman, Zeithaml, and Berry, namely tangibles, reliability, responsiveness, assurance, and empathy. The research uses a descriptive qualitative approach with a case study method. Primary data was obtained through in-depth interviews with the BPD chairperson, village officials, and BPD members, while secondary data was sourced from official village documents, accountability reports, and related literature. Data analysis was conducted using the interactive Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing.The results of the study indicate that in the tangibles dimension, the BPD has provided physical facilities and information media that support transparency; in the reliability dimension, the BPD consistently carries out supervision in accordance with the planning and implementation cycle of village programs; in the responsiveness dimension, the BPD quickly responds to complaints and aspirations from the community; in the assurance dimension. Factors supporting the role of the BPD include the commitment of members to transparency, clear regulatory support, and partnerships with village officials and the community. Meanwhile, the main obstacles include limited human resources, supporting facilities, and suboptimal community participation. In conclusion, the BPD of Kersik Tuo Village has played a fairly effective role in maintaining the accountability of village administration, although there is still a need to improve the capacity of members, strengthen facilities and infrastructure, optimize public participation, and utilize information technology to support transparency and the quality of village public services.